Research on the Mathematical Competence of Lithuanian Primary School Pupils - Dagienė, Valentina; Vinikienė, Lina; Sutkutė, Elena (Information & Media, 2018)
The assesment of the mathematics achievements of pupils in Lithuanian primary education (lower secondary schools) is a topical issue. The paper deals with Lithuanian standardized math tests for 8th graders and the international PISA survey of 15-year-old students. The survey on investigating the students’ mathematical abilities, together with the factors influencing them, was conducted. Some information on the learning outcomes is provided. We have focused on explaining how standardized mathematical tests are made using the item response theory (IRT). In addition, how the Rasch model is applied to count the results of the PISA survey. The results of the 8th grade standardized tests in mathematics of 2015 and the PISA surveys of 2012, as well as the PISA 2015 mathematical literacy results, are all discussed. Some samples of set of tests are provided and further analyzed.
Keywords: standardized tests; PISA; item response theory (IRT); Rasch model